Au-Ag bimetallic catalysis: 3-alkynyl benzofurans from phenols via tandem C-H alkynylation/oxy-alkynylation - Hu, Long; Dietl, Martin C.; Han, Chunyu; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2021)
The development of new methodologies enabling a facile access to valuable heterocyclic frameworks still is an important subject of research. In this context, we describe a dual catalytic cycle merging C−H alkynylation of phenols and oxy-alkynylation of the newly introduced triple bond by using a unique redox property and the carbophilic π acidity of gold. Mechanistic studies support the participation of a bimetallic gold-silver species. The one-pot protocol offers a direct, simple, and regio-specific approach to 3-alkynyl benzofurans from readily available phenols. A broad range of substrates, including heterocycles, is transferred with excellent functional group tolerance. Thus, this methodology can be used for the late-stage incorporation of benzofurans.